Seasonal Population Fluctuation and Sex Ratio of Frankliniella occidentalis on Greenhouses Melon in Arid Southeastern of Algeria, North Africa - Farid Allache; Fatma Demnati; Sabah Razi (Universitas Andalas, 2026)
The western flower thrips, Frankliniella occidentalis (Pergande 1895), is a polyphagous and invasive pest that causes serious damage to greenhouse crops. The present study aimed to examine the population changes, relative abundance, sex ratio, and species composition of thrips associated with melon (Cucumis melo L.) cultivated under greenhouse conditions in Garta, Algeria. Populations of F. occidentalis were monitored weekly from February to June 2017. Thrips densities increased with temperature; however, correlations with temperature (r = 0.54–0.55, p > 0.05) and relative humidity (r = 0.10–0.24, p > 0.05) were weak and not significant. Adults predominated on leaves, while larvae were less abundant (mean 7.44 per 30 leaves). High relative abundance was recorded across all sampling methods. Females largely predominated, accounting for 90.81–91.28% of adults, corresponding to a male-to-female ratio of approximately 1:9. Six thrips species were identified from the melon crop, with F. occidentalis being the dominant species. The other species included Odontothrips loti, Aeolothrips intermedius, Thrips minutissimus, Melanthrips fuscus, and Chirothrips manicatus, along with a few tubuliferous individuals. These results provide new insights into the population dynamics of F. occidentalis under arid greenhouse conditions and contribute to a better understanding of its prevalence in North African cropping systems.